Quality of Soil and Yield of Food Crops in Ultisols Due to Application of Manure and Source of Phosphate Fertilizer - Soelaeman, Yoyo; Haryati, Umi (JOURNAL OF TROPICAL SOILS, 2012)
Acid upland soil in Indonesia has a potential for agricultural development but it has constraints low of organic C and available P as well as the soil physical properties have been degraded. The use of manure and direct application phosphate rock (PR) was an alternative to improve land productivity and crop yields. The objective of the study was to examine the effects of manure and the sources of P on soil physical and chemical properties and yield of foods crop that was arranged on intensive cropping systems of upland rice + maize -/- cassava- mungbean. The experiment was carried out at Tamanbogo Station Farm, East Lampung since 2007 until 2009 using randomized completely block design with 3 replications. The treatments were (1) 10 Mg ha-1 manures + 1 Mg ha-1 of RP, (2) without manure + 1 Mg ha-1 of PR, (3) 10 Mg ha-1 manures + 100 kg ha-1 SP 36, and (4) without manure + 100 kg ha-1 SP 36. The results showed that the application of manure along with PR improved soil chemical and physical characteristics. Its improvement affected the yield of foods crops, hence the profit increased with B/C ratio between 2.88-3.60.